2020
DOI: 10.7759/cureus.8163
|View full text |Cite
|
Sign up to set email alerts
|

Highlighting Survival with Yttrium-90 Radioembolization Therapy in Unresectable Hepatocellular Carcinoma

Abstract: Unresectable hepatocellular carcinoma has several different therapeutic options, including targeted agents as well as locoregional therapy. Yttrium-90 (Y90) radioembolization therapy is an established treatment for unresectable disease and has been compared to other locoregional options as well as different targeted therapies. Newer case series are also reporting a potential benefit to the addition of immunotherapy to Y90 radioembolization. Here we report a case of prolonged survival in a patient whose treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…15 Sorafenib, an antiangiogenic agent, also normalizes tumor vasculature and improves the delivery of oxygen to the tumor which complements the immunogenic effect of Y90 radioembolization. 10 The main limitation of our study is the small reported number of HCC patients with HV or IVC invasion that have undergone Y90-systemic combination therapy. Moreover, the optimal interval and dosage of sorafenib or nivolumab when used with Y90 radioembolization have not been fully explored.…”
Section: Discussionmentioning
confidence: 91%
“…15 Sorafenib, an antiangiogenic agent, also normalizes tumor vasculature and improves the delivery of oxygen to the tumor which complements the immunogenic effect of Y90 radioembolization. 10 The main limitation of our study is the small reported number of HCC patients with HV or IVC invasion that have undergone Y90-systemic combination therapy. Moreover, the optimal interval and dosage of sorafenib or nivolumab when used with Y90 radioembolization have not been fully explored.…”
Section: Discussionmentioning
confidence: 91%
“…This included 11 clinical trials (4 randomized and 7 nonrandomized) and 8 cohort studies (Table 1), 12 case series, and 32 case reports (supplemental online Table 3). Fifty of the articles described the use of immunotherapy agents in the setting of unresectable HCC [13, 14, 18, 29–75], 3 in the neoadjuvant setting [76–78], and 10 in the setting of LT [79–88], and they reported on 2,402 patients in total (Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
“…The mean score of the NHBLI scale for the case series [31, 32, 37, 39, 40, 44, 51, 62, 67, 77, 80, 84] was 6.8 ± 0.9 (supplemental online Table 6). The mean score of the JBI scale for the case reports [29, 33, 34, 38, 41, 43, 46–50, 52, 55, 61, 64, 65, 68, 69, 71, 72, 74–76, 78, 79, 81–83, 85–88] was 7.2 ± 1.1 (supplemental online Table 7). These results highlight that the included studies were of high quality on average.…”
Section: Resultsmentioning
confidence: 99%
“…However, the subsequent phase I and phase II clinical investigation [160] and several retrospective studies [15,161,162] have revealed the safety and efficacy of TARE using 90 Y isotope-loaded particles in the treatment of HCC. Specifically, the HCC patients treated with TARE showed similar therapy responses compared to alternative therapies including cTACE, TACE, and chemotherapy (sorafenib) [163][164][165][166]. In general, TARE is becoming a promising treatment option for unresectable primary or secondary liver malignancies [152,167].…”
Section: Microspheres For Radioembolizationmentioning
confidence: 97%